Reliability Evaluation and Preventive Maintenance Strategy Selection of Traction Substation Equipment Considering Its Wear Degree - E. E. Bakeev; A. I. Sharapova (Вестник Научно-исследовательского института железнодорожного транспорта)
Existing testing and preventive maintenance pattern is meant for the equipment which actual term of service does not exceed the maximum allowable one. As a result traction substations’ fault rate increases year on year. One reason for this proves to be ageing of equipment, which is supported with statistical data obtained from the data bases of Automated Power Supply Control System (ASUE) and Comprehensive Automated System for Record Keeping and Fault Elimination Monitoring of the JSC RZD Technical Facilities and Analysis of Their Reliability (KASANT). Today optimization of preventive maintenance pattern is a rather important task. It is a challenging task so far as the existing diagnostic techniques do not deliver complete information on the equipment reliability and it is necessary to find optimum maintenance strategy in terms of incomplete system condition data. The paper tackles the selection problem of optimum preventive maintenance pattern of traction substation equipment making allowance for its ageing. It is also indicated that the system states describing process is a regenerating one. That’s why average unit losses in terms of unlimited (“endless”) system service life can be defined by the ratio between the average losses over the inter-maintenance period and the length of this period. There is described algorithm for optimum schedule formation of the equipment preventive maintenance. Approximate solution of the problem in terms of unlimited service life of the system can be obtained through use of the reliability mapping based URRAN procedure developed by the JSC NIIAS (Research & Design Institute for Information Technology, Signalling and Telecommunications on Railway Transport).